Application of case-based reasoning in the support to the decision of a help DESK WEB SYSTEM (Revista Brasileira de Contabilidade e Gestão, 2012)
This paper presents the development of a web help desk using the technique of artificial intelligence Case Based Reasoning (CBR). The system is applied in the field of technical help desk from a company developer of business automation applications. Using the Java programming language in conjunction with web development frameworks, the system was developed to assist in decision support technicians involved with customer service.
Keywords: MVC; JPA; Java; Web; decision support systems; artificial intelligence; case based reasoning